A SOCIOCULTURAL APPROACH TO LANGUAGE LEARNING AND INTERDISCIPLINARITY IN STARDEW VALLEY - Rocha Cruz, Fabielle (Revista de Educação do Vale do São Francisco, 2020)
As the digital world has constantly been a part of the reality of so many children, finding a way to use it in favor of school and the learning process is a common goal. This article aims to present a perspective in the sociocultural approach according to Vygotsky and the possibilities of using the digital game Stardew Valley in a language lesson, to present context, meaning and word choice related to any possible subject, for example, through its interaction mechanics and using the second language as the means to do so. After the literature review, which introduces to the views related to the use of games and the sociocultural approach, the author presents the methods and a corpus analysis regarding sentences that are part of the game and can be used to focus on understanding language use. The analysis suggests the game proposed could be a valuable asset for the language learning class, as long as teachers use it as an extension of their classes, creating a critical reflection on the gameplay, as well as working alongside other teachers and subjects from the core curriculum.